PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK SISWA SDN 034791 TANJUNG BERINGIN - Malau, Lidia; Nurmayani, Nurmayani; Lubis, Wildansyah; Sitohang, Risma; Prawijaya, Septian (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to see the influence of learning media Puzzles to improve student thematic learning outcomes at SDN 034791 Tanjung Beringin FY 2022/2023. This type of research is pre-experimental designs research with one group pretest posttest research form. The subjects of this research were sixth grade students totaling 20 students at SDN 034791 Tanjung Beringin. Instruments used in Student learning activities were previously tested to determine validity and reliability test. Instruments were given before and after providing puzzle learning media. Technique The analysis carried out is the normality test and hypothesis test, namely the t-test. Before Hypothesis testing is carried out, first a prerequisite test is carried out, namely the normality test. Based on the results of the prerequisite test calculations, the pre-test data obtained an average of posttest results of 49.95 obtained results of 79.2, which means both values are > 0.05 so it can be It is said that both data are normally distributed. Next is done Hypothesis testing and research results show tcount = 29.99 and ttable = 11.68. From From this data it can be seen that tcount > ttable, namely 29.99 > 11.68. This is meaningful Ha is accepted then there is a significant influence from media use Puzzle learning to improve the learning outcomes of fourth grade students at SDN 034791 Tanjung Beringin, Tigalingga District, Dairi Regency FY 2022/2023. Keywords: Learning Outcomes, Puzzle Learning Media